Sowing Rates and Methods Affect Yield and Forage Quality of American Jointvetch in the Southwestern Area of Japan - Manabu Tobisa; Yutaka Nakano (Agronomy)
This research aimed to assess how different sowing methods and seeding rates influenced the growth, yield characteristics, and forage nutritional value for establishing American jointvetch, a tropical forage legume known for its high productivity and quality, in grasslands in southwestern Japan. The experimental treatments involved two sowing methods, row sowing (RS) and broadcast sowing (BS), and combinations of four different seeding rates (SR, 5, 10, 20, or 30 kg ha−1). The sowing methods affected dry matter yield (DMY): BS resulted in higher DMY (11.3 vs. 8.7 t DM ha−1) and leaf area index (LAI, 7.2 vs. 5.3) than RS, respectively. However, in vitro dry matter digestibility (IVDMD) and crude protein (CP) concentrations were not influenced by the sowing methods. The SR affected LAI, particularly RS, and LAI increased with increasing SR. Contrary to expectations, SR did not affect DMY, IVDMD, CP, digestible DMY, or CP yield. The findings of this investigation indicate that broadcast sowing is the superior method for planting, and even when using a reduced seeding rate of 5 kg ha−1 of seed-in-pod, there was no significant impact on the yield or forage quality of American jointvetch under the conditions examined in this study. This information will contribute to the proper management of its cultivation to ensure higher productivity for use as livestock fodder.